2016
DOI: 10.1002/rra.3032
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial Corridor Changes Over Time in Regulated and Non‐Regulated Rivers (Upper Esla River, NW Spain)

Abstract: Over the last decades, rivers and fluvial corridors have been noticeably modified from their natural conditions. In general, damming and other in-channel human interventions have been traditionally considered as the main drivers of change. However, recent studies highlight the influence of climate, hillslope and floodplain cover changes over fluvial corridor dynamics. The present study illustrates the channel morphology and riparian vegetation responses observed in three gravel bed rivers located in the Upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
1
22
0
2
Order By: Relevance
“…flow regulation by dams and reservoirs, could also act synergistically with climate change, inducing similar biogeomorphic responses on fluvial landscapes. The extensive literature on damming effects includes multiple examples of channel narrowing and vegetation encroachment (Graf, ; Bejarano et al ., ; González del Tánago et al ., ; Martínez‐Fernández et al ., ) which in many cases could become reinforced by climate change. Hence we argue that river impacts should be assessed at multiple scales, and that persistent long‐term and large‐scale pressures like climate change must be taken into account when diagnosing problems induced by small‐scale pressures, in order to strategically design realistic rehabilitation goals and sustainable mitigation or adaptation measures.…”
Section: Discussionmentioning
confidence: 99%
“…flow regulation by dams and reservoirs, could also act synergistically with climate change, inducing similar biogeomorphic responses on fluvial landscapes. The extensive literature on damming effects includes multiple examples of channel narrowing and vegetation encroachment (Graf, ; Bejarano et al ., ; González del Tánago et al ., ; Martínez‐Fernández et al ., ) which in many cases could become reinforced by climate change. Hence we argue that river impacts should be assessed at multiple scales, and that persistent long‐term and large‐scale pressures like climate change must be taken into account when diagnosing problems induced by small‐scale pressures, in order to strategically design realistic rehabilitation goals and sustainable mitigation or adaptation measures.…”
Section: Discussionmentioning
confidence: 99%
“…These vegetation communities were not yet present (or did not have adult form) in the 1994 aerial photograph but appeared clearly consolidated in the 2000 image, after a long period without floods (1993–2001) that could have favoured vegetation development at the flowing channel banks. In another river of the region affected by damming, the Mijares River, Garófano‐Gómez et al () observed a period of the same duration (40 years) between reservoir construction and the completion of the process of encroachment of dense woody vegetation, whereas Martínez‐Fernández et al () have identified a similar stage of stability between 2000 and 2015 in Northwestern Spain.…”
Section: Discussionmentioning
confidence: 99%
“…According to Braatne et al (), although the combination of the three methods is the best option, the pre‐ versus post‐dam approach provides the most reliable results. This approach is endorsed by several works that have explored historical river channel adjustment processes after damming (Surian, ; Magdaleno, Anastasio Fernández, & Merino, ; Scorpio et al, ; Scorpio & Roskoff, ; Martínez‐Fernández, González del Tánago, Maroto, & García de Jalón, ; Arnaud et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…The reach‐scale analysis of vegetation changes in regulated and unregulated river reaches shown by Martínez‐Fernández et al (), confirms that a better understanding of sediment‐flow interactions with the riverbed substrate and the riverbanks are crucial to understand large‐scale processes induced by afforestation changes, farmland abandonment and construction of dams. This is clear in their long‐term analysis of ortho‐photos over several decades since the 1950's, from a morphological (e.g.…”
Section: Upscaling Microhabitat Ecohydraulics At the Reach‐scalementioning
confidence: 97%